AKUNTANSI SYARIAH: SEBUAH TINJAUAN ANTARA TEORI DAN PRAKTIK - Hani Werdi Apriyanti (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2017)
Accounting theory is part of the accounting practices. A good understanding of accounting theory will encouragethe development of accounting to the accounting practices. Conceptually, Islamic accounting practices present asa solution to the problems of conventional transactions that are not in accordance with Islamic values. Thereforeneed more explanation about the various assumptions underlying the islamic accounting practices in Indonesia. Tounderstand and explain the islamic accounting practices applied Indonesia, it needs accounting theory approachto islamic Value.KeyWords : Islamic Accounting theory, Accounting Practices